1996
DOI: 10.1016/0304-3959(96)03016-3
|View full text |Cite
|
Sign up to set email alerts
|

CO2 laser activation of nociceptive and non-nociceptive thermal afferents from hairy and glabrous skin

Abstract: In 8 healthy subjects we have recorded cerebral evoked potentials and reaction time (RT) to CO2 laser stimulation of the hairy and glabrous skin at low and high stimulus intensities, corresponding to subjective reporting of detection and pain, respectively. At each intensity we were able to identify an evoked potential; the latencies of the major vertex positive (VP) components fell into 2 distinct populations 320 +/- 30 (VP300) and 778 +/- 80 (VP800) which did not differ between stimulation sites. The frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 19 publications
1
34
1
Order By: Relevance
“…In addition, our early and late time windows correspond well to latencies of A␦ and C fiber-mediated cortical responses in previous electroencephalographic studies (9)(10)(11)(12)(13) and to reaction times to first and second pain of about 400-500 and 1,000 ms, respectively (1, 2, 4, 7). Taken together, these points strongly suggest that early and late responses reflect perception of first and second pain, respectively.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, our early and late time windows correspond well to latencies of A␦ and C fiber-mediated cortical responses in previous electroencephalographic studies (9)(10)(11)(12)(13) and to reaction times to first and second pain of about 400-500 and 1,000 ms, respectively (1, 2, 4, 7). Taken together, these points strongly suggest that early and late responses reflect perception of first and second pain, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…Neurophysiological recordings in humans revealed early A␦ fibermediated activations in S1, S2, and ACC (for review, see ref. 8), whereas C fiber-mediated cortical responses at latencies of about 1,000 ms have been shown in scalp recordings (9)(10)(11)(12)(13) but have not yet been consistently localized. Conversely, functional imaging studies using tonic C fiber stimuli demonstrated activation of S1, S2, Insula, and ACC (14-17) but did not provide temporal information.…”
mentioning
confidence: 99%
“…Indeed, because the thermal activation threshold of C-fiber afferents is consistently lower than the thermal activation threshold of A␦-fiber afferents (difference, 2.3-3°C) (Plaghki et al, 2010), reducing the energy density of the laser stimulus constitutes one of the previously validated methods to activate C-nociceptors selectively (for review, see Plaghki andMouraux, 2002, 2005;Plaghki, 2007), and this approach has been already used successfully in several previous studies (Treede et al, 1995;Towell et al, 1996;Magerl et al, 1999;Agostino et al, 2000;Tran et al, 2002;Cruccu et al, 2003;Iannetti et al, 2003;Mouraux et al, 2003;Qiu et al, 2006;Mouraux and Plaghki, 2007).…”
Section: Steady-state Thermal Stimulation Of A␦-and C-nociceptorsmentioning
confidence: 99%
“…Although waveforms consistent with an ultralate (C-mediated) LEP have been recorded in the immediate wake of a late (Aδ-mediated) LEP, (Magerl et al, 1999) a fiber-specific origin of the suspected ultralate response could not be established; nor could an incomplete suppressive effect of the preceding Aδ response be ruled out. Indeed, Towell and colleagues (Towell et al, 1996) noticed that the ultra-late LEPs could be recorded most frequently when the stimulus intensity was low and the late LEPs less well identified. These observations support our finding that the mutually suppressive interaction depends on the magnitude of the conditioning stimulus.…”
Section: The Interaction Of Aδ and C Signals Is Intensity Dependentmentioning
confidence: 99%